The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5899/2017/dea-00145
|View full text |Cite
|
Sign up to set email alerts
|

On Characterizing weak defining hyperplanes (weak Facets) in DEA with Constant Returns to Scale Technology

Abstract: The Production Possibility Set (PPS) is defined as a set of inputs and outputs of a system in which inputs can produce outputs. The Production Possibility Set of the Data Envelopment Analysis (DEA) model is contain of two types defining hyperplanes (facets); strong and weak efficient facets. In this paper, the problem of finding weak defining hyperplanes of the PPS of the CCR model is dealt with. However, the equation of strong defining hyperplanes of the PPS of the CCR model can be found in this paper. We sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The studies of e cient frontiers and characterization of di erent types of hyperplanes have been less intensively investigated [10,11]. The connotation of the e cient frontier DMUs in the DEA was studied by Jahanshahloo et al [12]; this study found the piecewise linear frontier of the production function.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of e cient frontiers and characterization of di erent types of hyperplanes have been less intensively investigated [10,11]. The connotation of the e cient frontier DMUs in the DEA was studied by Jahanshahloo et al [12]; this study found the piecewise linear frontier of the production function.…”
Section: Introductionmentioning
confidence: 99%